Practical Approaches and Knowledge Gaps in the Care for Children With Leukodystrophies. (January 2021) - Keller, Stephanie R.; Mallack, Eric J.; Rubin, Jennifer P.; Accardo, Jennifer A.; Brault, Jennifer A.; Corre, Camille S.; Elizondo, Camila; Garafola, Jennifer; Jackson-Garcia, April C.; Rhee, Jullie; Seeger, Elisa; Shullanberger, Kaprice C.; et al.
Leukodystrophies are a group of neurodegenerative genetic disorders that affect approximately 1 in 7500 individuals. Despite therapeutic progress in individual leukodystrophies, guidelines in neurologic care are sparse and consensus among physicians and caregivers remains a challenge. At patient advocacy meetings hosted by Hunter's Hope from 2016-2018, multidisciplinary experts and caregivers met to conduct a literature review, identify knowledge gaps and summarize best practices regarding neurologic care. Stages of severity in leukodystrophies guided recommendations to address different levels of need based on a newly defined system of disease severity. Four core neurologic domains prioritized by families were identified and became the focus of this guideline: sleep, pain, seizures/epilepsy, and language/cognition. Based on clinical severity, the following categories were used: presymptomatic, early symptomatic, intermediate symptomatic, and advanced symptomatic. Across the leukodystrophies, neurologic care should be tailored to stages of severity while accounting for unique aspects of every disease and multiple knowledge gaps present. Standardized tools and surveys can help guide treatment but should not overburden families.